The effects of fluoride in the drinking water - Linuz Aggeborn; Mattias Öhman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
Fluoridation of the drinking water is a public policy whose aim is to improve dental health. Although the evidence is clear that fluoride is good for dental health, concerns have been raised regarding potential negative effects on cognitive development. We study the effects of fluoride exposure through the drinking water throughout life on cognitive and non-cognitive ability, math test scores and labor market outcomes in a large-scale setting. We use a rich Swedish register dataset for the cohorts born 1985-1992 in the main analysis, together with drinking water fluoride data. To estimate the effects, we exploit intra-municipality variation of fluoride, stemming from an exogenous variation in the bedrock. Taking all together, we investigate and confirm the long-established positive relationship between fluoride and dental health. Second, we find precisely estimated zero-effects on cognitive ability, non-cognitive ability and math test scores for fluoride levels in Swedish drinking water. Third, we find that fluoride improves later labor market outcomes, which indicates that good dental health is a positive factor on the labor market.
Keywords: I10; H42; I18; 330; Fluoride; Cognitive development; Labor market outcomes; Dental health